Peningkatan Kesadaran Masyarakat Terhadap Lingkungan di Desa Sibang Gede Kecamatan Abiansemal Kabupaten Badung - I Nyoman Sutama; I Gusti Bagus Suryawan; I Wayan Kartana (Universitas Warmadewa, 2025)
Sibanggede Village is one of the villages in Abiansemal Subdistrict. Geographically, Sibanggede Village is a lowland area, while to the north there are Sibang Kaja Village and Mekar Buana Village, which are located at higher elevations. As a result, during the rainy season Sibanggede Village receives waste carried from upstream areas. In addition, Sibanggede Village has a traditional market that produces waste every day, compounded by household waste management that has not yet been optimal. Therefore, the socialization of Badung Regency Regional Regulation No. 7 of 2013 concerning Waste Management is very urgent to be carried out in order to increase public awareness in waste management. Article 7 of Regional Regulation No. 7 of 2013 states that waste management is carried out through waste sorting, collection, transportation, processing, and final disposal. In terms of sorting and collection, the important roles of housewives (PKK), youth organizations (Karang Taruna), and area managers are essential. Meanwhile, in terms of transportation, processing, and final disposal, the policies lie with the Village Government and the Badung Regency Government (DLHK Office). Regarding waste management in Sibanggede Village, the village already has a Waste Bank and TPS3R facilities, as well as the commitment of housewives (PKK), represented by the PKK representative of Sibanggede Village, to assist with household waste sorting. Meanwhile, the Badung Regency Government (DLHK) will provide the necessary facilities, including residual waste processing through the construction of a TPSD in Mengwitani. Furthermore, the Warmadewa PKM team proposes that producers who manufacture packaged goods are obliged to manage their packaging waste. If this obligation is not fulfilled, it may be proposed that their business licenses be frozen or revoked, as regulated in Article 29 of Regional Regulation No. 7 of 2013 concerning Waste Management.